2022
DOI: 10.1186/s12909-022-03554-w
|View full text |Cite
|
Sign up to set email alerts
|

Empathy alleviates the learning burnout of medical college students through enhancing resilience

Abstract: Objective The problem of learning burnout of medical students is becoming prominent, and empathy can play a good predictive role in learning burnout. The present study aimed to investigate the relationship between empathy and learning burnout, as well as the mediation effect of resilience in this relation. Methods Five hundred and eighty-eighth college students from a key medical university in Yunnan Province was investigated using the Basic Empath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…In terms of the differences in the learning burnout reported by male and female undergraduate clinical medical students, male students had significantly higher overall scores. Their experience of learning burnout was more intense than that of their female counterparts, which is consistent with the findings of Wu et al [ 13 ] The questionnaire responses revealed that male students were more susceptible to distractions such as computers and online games after entering university, and had poor self-discipline. This lack of self-discipline manifests in behaviors such as arriving late for classes and leaving early, a lack of concentration, falling asleep, and habitual phone use during class, leading to a waning interest and motivation to study.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of the differences in the learning burnout reported by male and female undergraduate clinical medical students, male students had significantly higher overall scores. Their experience of learning burnout was more intense than that of their female counterparts, which is consistent with the findings of Wu et al [ 13 ] The questionnaire responses revealed that male students were more susceptible to distractions such as computers and online games after entering university, and had poor self-discipline. This lack of self-discipline manifests in behaviors such as arriving late for classes and leaving early, a lack of concentration, falling asleep, and habitual phone use during class, leading to a waning interest and motivation to study.…”
Section: Discussionsupporting
confidence: 89%
“…However, based on the finding that the emotional exhaustion factor of burnout [53] is in the opposite pole of the JSE scores factor [35], we expect to find an inverse association between cognitively defined clinical empathy (measured by the JSE) and indicators of burnout experiences, and a positive association between a measure of emotional empathy and burnout. This expectation was indeed confirmed in a study in which it was reported that a cognitive empathy measure, as opposed to emotional empathy, significantly predicted a lower degree of burnout and stronger mental resilience in medical students [69].…”
Section: Clinical Empathy and Qualities Detrimental To Interpersonal ...mentioning
confidence: 57%
“…The dispositional mindfulness‐psychological resilience‐learning burnout model is only a sub‐model of mindfulness intervention based on JD‐R theory. For example, Previous studies have found that learning burnout and dispositional mindfulness are closely related to psychological stress, cognitive emotion regulation, empathy, job satisfaction, depression, and anxiety (Chen, 2021; Koutsimani et al, 2019; Liu et al, 2022; Mesmer‐Magnus et al, 2017; Wu et al, 2022). Therefore, future studies should consider building mediation models of these factors between dispositional mindfulness and learning burnout or constructing more complex multiple mediation models.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as a personal internal resource, psychological resilience often acts as a mediating bridge between psychological problems and their internal/ external influencing factors (Liu et al, 2017). It cannot only alleviate the adverse effects of learning stress (Liu et al, 2018), psychological overrun (Zhefeng, 2019), and negative cognitive emotional regulation (Chen, 2021) on learning burnout but also enhance the positive effects of empathy (Wu et al, 2022), trait emotional intelligence (Fiorilli et al, 2017), learning motivation (Zheng, 2021), and positive cognitive emotional regulation (Chen, 2021) on learning burnout.…”
Section: Introductionmentioning
confidence: 99%